Shocks Abroad, Pain at Home? Bank-Firm Level Evidence on the International Transmission of Financial Shocks - Steven Ongena; José-Luis Peydró; Neeltje van Horen (IMF Economic Review, 2015)
We study the international transmission of shocks from the banking to the real sector during the global financial crisis. For identification, we use matched bank-firm level data, covering mainly small and medium-sized firms in Eastern Europe and Turkey, and exploit the Lehman failure. We find that internationally-borrowing domestic and especially foreign-owned banks contract their credit more during the crisis than locally-funded domestic banks do. Firms dependent on credit and with a relationship with internationally-borrowing domestic or foreign banks suffer more in their financing and real performance; especially when single-bank, small or with limited tangible assets. Moreover, firms in countries with lower financial development, more reliance on foreign funding and slower contract enforcement are more affected. Overall our results suggest the existence of spillovers to the real sector through an international banking channel but with heterogeneous effects across firms and countries.
Keywords: G01; G21; F23; F36; 330; international transmission; firm real effects; foreign banks; international wholesale funding; credit shock